Cardiovascular risk factors in patients with combined central retinal vein occlusion and cilioretinal artery occlusion: Case report. Issue 1 (January 2018) - Grzybowski, Andrzej; Elikowski, Waldemar; Gaca-Wysocka, Magdalena
Abstract: Rationale: To analyze cardiovascular risk factors and comorbidity of acute unilateral visual loss due to combined central retinal vein occlusion (CRVO) and cilioretinal artery occlusion (CLRAO). Patient concerns: Among patients with retinal vein or artery occlusion hospitalized at the Department of Ophthalmology between January 2011 and August 2017, subjects with combined CRVO/CLRAO were selected. All of them underwent ophthalmologic and cardiologic examination, including fluorescein angiography, optical coherence tomography, 12-lead electrocardiogram, transthoracic and transesophageal echocardiography, carotid Doppler sonography, cerebral magnetic resonance imaging, and a panel of laboratory tests. Diagnoses: Four subjects with coexisting CRVO and CLRAO were found among 146 patients with retinal vein or artery occlusion. There were no other types of concomitance of CRVO and retinal artery occlusion. Interventions: All patients were treated with low molecular heparin in a full dose for 2 weeks, then with 1 mg/kg once daily for the next 2 weeks, followed by acetylsalicylic acid 75 mg/kg/d. Other medication included long-term statins, angiotensin-converting-enzyme inhibitor in 3 patients and beta-blocker in one patient. Outcomes: All patients with CRVO/CLRAO presented multiple cardiovascular risk factors, including hypertension, obesity, hyperlipidemia, chronic nicotine addiction, and a positive family history of coronary artery disease or stroke. In all of them, echocardiography revealed left ventricular hypertrophy and atherosclerotic lesions in the descending aorta; in addition, 3 patients had insignificant atherosclerotic plaques in the carotid artery. Also, in 3 subjects, focal ischemic cerebral changes were diagnosed. Lessons: Patients with combined CRVO and CLRAO present numerous cardiovascular risk factors and abnormalities on imaging examinations, which should be routinely evaluated and treated.